Analytical hierarchy approach for load shedding scheme: a case study based on the Johor System - Ling, Chak Ung (2012)
In general, the highly development environment in the society or the natural interruptions can cause loss of the power supply due to the burden of the generator. In industries, this can cause million of losses when the shortage of supply occurs. Usually, the supply will be back-upped in the storage system. If the over demand is uncontrolled, or when there is no decision-making in removing a certain load, there will be a trouble in the power system. Certain loads will be removed depending on some importance or criteria such as operating load and area power. This requires some decision-making in order order to choose the best load(s) to be cut off. In order to do that, Multi Criteria Decision Making (MCDM) can be applied in determination of the load shedding scheme in the electric power system. The objective of this thesis is to justify a load shedding scheme for an islanded power system. This thesis proposes methodologies for load shedding scheme for the islanded electric power system by using Analytic Hierarchy Process (AHP), Fuzzy Analytic Hierarchy Process (Fuzzy AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). In this thesis, the load shedding scheme is applied to several systems such as large pulp mill electrical system, IEEE 118 bus test case system, Selangor electrical system and Johore electrical system. Models are built up on the base of analysing correlative factors with examples given to indicate how the AHP, Fuzzy AHP and TOPSIS are applied. From this thesis, a series of analyses are conducted and the results are determined. Analyses are made, and the results have shown that AHP, Fuzzy AHP and TOPSIS can be used in determination of the load shedding scheme in pulp mill system, IEEE 118 bus system, Selangor system and Johore system. Among these three MCDM methods, the results shown by TOPSIS is the most effective solution because of the effectiveness of load shedding is the highest.